Global climate justice: the case of climate migrants - Van Heerden, Samantha Jane Ashburner (Rhodes University, Faculty of Humanities, Department of Philosophy)
Climate change is predicted to displace thousands of people across the globe. Due to their geographical location and limited resources available for adaptation, this will particularly impact those in developing states, who might have to flee from the growing frequency and severity of rising sea levels, drought and desertification, and acute natural disasters such as floods, wildfires, and hurricanes. This is likely to have pervasive effects on the moral interests of those affected, threatening loss of life, the deterioration of livelihoods, and for small island states even complete or substantial loss of state territory. In this thesis I will argue that we should conceive of this situation as a problem of global justice. Though some argue that questions of justice only arise within the state, I will argue that global economic and political institutions have contributed to the plight of climate migrants, and that following from Darrel Moellendorf's theory of associational justice, this enduring impact results in an association and duties of justice that transcend state borders. To respect the dignity of climate migrants, such an unjust association needs to be rectified by establishing ethical principles that could be reasonably endorsed by everyone affected. Drawing from Gillian Brock, I will argue that the best way to rectify the situation is through establishing a principle of distributive justice which focuses on 'agency needs': needs whose fulfilment is necessary for human agency. Using this framework, I then provide some recommendations of what is owed to climate migrants to achieve justice for them. I also consider how these duties of justice should be distributed, first critiquing a dominant approach that attributes duties primarily to polluters. In the end, I recommend that duties should be dispersed between all those who support the global institutions responsible, those who have been high polluters since 1990, and the most affluent in the world. As the effects of climate change become increasingly pronounced within the next fifty years, establishing what is owed to those displaced is of utmost importance, and I hope this thesis shows how normative philosophy can help us think through these urgent questions.
Keywords: Climate justice; Environmental refugees; Climatic changes -- Social aspects; Applied ethics; Political science -- Philosophy; Refugees; Global justice; Relocation (Housing) -- Environmental aspects